Benefits management for an e-invoice process - Almeida, José Carlos P. (2010)
This paper presents the application of a Benefits Management (BM) Methodology to an e-lnvoice project, and analyzes the results brought forth by the application of the methodology to the project and its contribution towards a wider adoption in the targeted Organization. A Case Study research method has been used which began with a gathering and treatment of data related to the emission and reception of the invoices, continued with the identification of the type of investment and ended with the application of the chosen BM approach. The methodology demonstrated the financial viability of the project, identified and structured the resulting benefits and facilitated the understanding and preparation for the required transformations in the Organization, including processes, competencies/skills and technologies. The BM approach brings to the Organization a more wide and consolidated vision for the projects, a greater foresight and support for a rational decision on IS/IT investments and the strategic alignment of resources with the company objectives and priorities.